2019
DOI: 10.1177/1528083719868170
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers of poly (acrylonitrile-co-itaconic acid)/silver and polyacrylonitrile/silver:In situpreparation, characterization, and antimicrobial activity

Abstract: In this study, it was aimed to prepare silver nanoparticles by reduction of silver salt (AgNO3) in situ by means of only synthesized polyacrylonitrile (PAN) and poly(acrylonitrile-co-itaconic acid) (P(AN-co-IA)) polymers, and N,N dimethylformamide (DMF). Thereafter, PAN/Ag and P(AN-co-IA)/Ag nanofibers were prepared via electrospinning. Spectroscopic and morphologic characterizations, electrical and thermal features, and antimicrobial activities of the prepared nanofibers against Staphylococcus aureus, Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…It was shown that all nanocarriers prolonged vitamin E release but best by solid lipid nanoparticles from cosmetototextile products for use in skin cell repair and restoration for ocular area. Due to having large surface area, very small diameters, high loading efficiency and sustained release properties, electrospun nanofibers are one of the promising cosmetotextiles in recent years 34, 35 . In a study, electrospun poly (vinyl alcohol)/chitosan nanofibers incorporated with a combination of polyphenol-rich-herbal extracts was developed for use in facial acne treatment.…”
Section: Recent Studies On Cosmetotextilesmentioning
confidence: 99%
“…It was shown that all nanocarriers prolonged vitamin E release but best by solid lipid nanoparticles from cosmetototextile products for use in skin cell repair and restoration for ocular area. Due to having large surface area, very small diameters, high loading efficiency and sustained release properties, electrospun nanofibers are one of the promising cosmetotextiles in recent years 34, 35 . In a study, electrospun poly (vinyl alcohol)/chitosan nanofibers incorporated with a combination of polyphenol-rich-herbal extracts was developed for use in facial acne treatment.…”
Section: Recent Studies On Cosmetotextilesmentioning
confidence: 99%
“…Nanofibers mats can be prepared by electrospinning method and applied in several fields including filtration 17 , drug delivery 5 , nanosensors 18 and wound dressing as well 1 , 5 . Electrospinning enables the production of fibers from a wide range of polymers 19 , 20 or polymers blends with antibacterial agents 1 , 5 while allowing control over the properties of the nanofiber mat, such as the fiber’s size distribution, porosity, or mat thickness 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] PAN can be effectively used in nanocomposites and carbon bre production, and can also be used in a copolymer form for bre productions. 24 To produce antimicrobial electrospun nanobers, antimicrobial components can be integrated into nanobers during the electrospinning procedure. The antimicrobial effects were observed from electrospun nanobers integrated with silver nanoparticles (Ag NPs), 25 chitosan-silver NPs, 16 graphene oxide, 26 cinnamaldehyde, 27 antimicrobial peptides, 28 etc.…”
Section: Introductionmentioning
confidence: 99%
“…20–23 PAN can be effectively used in nanocomposites and carbon fibre production, and can also be used in a copolymer form for fibre productions. 24…”
Section: Introductionmentioning
confidence: 99%